Facing the deepest darkness of despair and abandonment : Psalm 88 and the life of faith - Mare, Leonard P. (Old Testament Essays, 2014)
Psalm 88 has been called an embarrassment to conventional faith. The psalm is unique when compared with other psalms of lament. In Ps 88 we find the desperate cry of someone who seeks to connect with YHWH, but YHWH keeps silent. The psalmist finds himself in the deepest darkness of abandonment and despair. Yet, his unanswered cry does not silence the poet. YHWH may stay quiet, but not the psalmist. He continues to hurl his cries into an empty sky, convinced that even in the face of YHWH's inattention, YHWH must still be addressed. Even when confronted with the reality of death, death caused by YHWH, the poet sticks to his protest, to be met yet again with more silence. YHWH doesn't speak, He doesn't act, and He doesn't care. The poet is ignored, snubbed, shunned, and rejected. The last word he speaks is darkness. What should one do about this complete silence and this bottomless darkness? What is this psalm doing in the Bible? What does this psalm say about the life of faith? What should one's response be when facing this dark night of the soul? Should one abandon God in the face of his desertion? This paper argues that Ps 88 stands as a signpost for realism in the life of faith.
free